2020
DOI: 10.1097/gox.0000000000002581
|View full text |Cite
|
Sign up to set email alerts
|

Gender Bias in the Integrated Plastic Surgery Residency: A Snapshot of Current Trends

Abstract: Introduction: According to the American Society of Plastic Surgeons, the male to female ratio of plastic surgeons is approximately 5:1. As more surgical specialties are recruiting female residents, there has been an increase in the amount of females. We set out to examine the current trends in residency recruitment and whether a quantifiable gender bias exists. Methods: A review of all the integrated plastic surgery programs within the United States was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…In total, 13 papers50–62 concentrated on gender discrimination during the process of residency application, including recommendation letters51–55 and interview,56–60 and fellowship applications 61,62. In standardized letters of recommendation most of these differences seem to disappear 52.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 13 papers50–62 concentrated on gender discrimination during the process of residency application, including recommendation letters51–55 and interview,56–60 and fellowship applications 61,62. In standardized letters of recommendation most of these differences seem to disappear 52.…”
Section: Resultsmentioning
confidence: 99%
“…From A complete list of BOD members was available for 10 out of 15 societies, and 6 out of 15 societies for committee chair positions. In order to assign gender, traditional naming conventions were utilized [6,7]. Web searches via Google were performed for photos in cases of gender-ambiguous names.…”
Section: Methodsmentioning
confidence: 99%
“…11 In comparison, from 2011 to 2020, the percentage of female trainees in general surgery programs increased from 36.2% to 43.1% in one study, whereas a separate study found that women compose 39% of plastic surgery residents. 13,14 Although progress is to be made, the relatively increased representation in hand surgery is promising, as increased female representation at higher levels of leadership generally correlates with increased representation at all levels within an institution. 12,15 Orthopedic surgery has trailed other surgical subspecialties in racial/ethnic diversity of trainees as well.…”
Section: Discussionmentioning
confidence: 99%